2015
DOI: 10.1021/acscentsci.5b00279
|View full text |Cite
|
Sign up to set email alerts
|

Fuel-Controlled Reassembly of Metal–Organic Architectures

Abstract: Many examples exist of biological self-assembled structures that restructure in response to external stimuli, then return to their previous state over a defined time scale, but most synthetic investigations so far have focused on systems that switch between states representing energetic minima upon stimulus application. Here we report an approach in which triphenylphosphine is used as a chemical fuel to maintain CuI-based self-assembled metallosupramolecular architectures for defined periods of time. This meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
70
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(72 citation statements)
references
References 53 publications
0
70
0
Order By: Relevance
“…3a). 11,[26][27][28][29][30][31][32][33][34] Here, a chemical fuel (F) reacts -either covalently or noncovalentlywith monomer M leading to an activated monomer M* which has the ability to aggregate (A* n ) in a thermodynamically favored process. Contemporaneously a backward reaction takes place which converts M* (or A* n ) back to M (or A n ) accompanied by the release of waste (W).…”
Section: Fig 3 ‫|‬ Dissipative Self-assembly Amentioning
confidence: 99%
“…3a). 11,[26][27][28][29][30][31][32][33][34] Here, a chemical fuel (F) reacts -either covalently or noncovalentlywith monomer M leading to an activated monomer M* which has the ability to aggregate (A* n ) in a thermodynamically favored process. Contemporaneously a backward reaction takes place which converts M* (or A* n ) back to M (or A n ) accompanied by the release of waste (W).…”
Section: Fig 3 ‫|‬ Dissipative Self-assembly Amentioning
confidence: 99%
“…Synthetic chemical‐fuel driven self‐assembly processes have been reported that also rely on noncovalent interactions between the building blocks and a chemical fuel . However, while most cases allude to similarities with microtubule formation or related biological dissipative processes, it turns out that in all the cases reported so far, a fundamentally different mechanism is operative (Figure b) . Contrary to what happens in Nature, energy dissipation, intended as the release of energy stored in the chemical fuel, is not catalysed by the building blocks, but rather by external elements such as an enzyme.…”
Section: Figurementioning
confidence: 99%
“…The same group used the sub‐component self‐assembly method to generate a tricopper(I) triangular macrocycle from nickel(II)‐porphyrin‐containing diamine, 2‐formylpyridine and [Cu(CH 3 CN) 4 ](OTf) . The UV/Vis and 1 H NMR experiments confirmed that the macrocycle binds 1 equivalent of C 60 .…”
Section: Discussionmentioning
confidence: 99%
“…The same group used the sub-components elf-assembly methodt og enerate at ricopper(I) triangular macrocycle from nickel(II)-porphyrin-containing diamine, 2-formylpyridine and [Cu(CH 3 CN) 4 ](OTf). [36] The UV/Vis and 1 HNMR experiments confirmed that the macrocycle binds 1equivalent of C 60 .A ddition of triphenylphosphine (PPh 3 )t ot he host-guest adduct, caused the formation of ah eteroleptic dicopper(I) complexc ontaining coordinated PPh 3 ligands, and released the C 60 .T he process could be reversed by oxidizing the coordinated PPh 3 ligands to triphenylphosphine oxide (O=PPh 3 ), this was accomplished using ar heniumc atalysta nd pyridine N-oxide ( Figure 15). The binding and releasec ould be carried out multiple times using PPh 3 as achemical fuel to cycle the process.…”
Section: Partial Disassemblyofthe Hostmentioning
confidence: 99%